Development of noble metal-free electrocatalysts towards acidic water oxidation: From fundamental understanding to state-of-the-art catalysts - Jing Ni; Zhaoping Shi; Yibo Wang; Jiahao Yang; Hongxiang Wu; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (eScience)
The development of low-cost and efficient electrocatalysts for oxygen evolution reaction (OER) in acid electrolytes is critical to the widespread implementation of proton electrolyte membrane water electrolyzers (PEMWE) towards carbon neutralization. Noble metal Ir- and Ru-based materials are state-of-the-art catalysts but still suffer from prohibitive price and scarcity. In this context, a variety of noble metal-free catalysts have been developed to decrease the cost of PEMWE. In this review, we first summarize the activity expression mechanism and stability issues for non-precious metal catalysts, highlighting the origins of performance degradation and the possible mitigation strategies. Then, we systematically review several recently developed noble metal-free catalysts, focusing on the design rationale and the structure-performance relation. Finally, the development prospects of non-noble metal catalysts are prospected, with the potential challenges for practical applications presented.